Methods of Badiuzzaman Sa’id Nursi to Understand Hadith in Kitab Rasail Al-Nur - Burhanuddin, Burhanuddin; Safri, Edi; Hakim, Luqmanul; Erizal, Arif Hendra; Dalil, Fitriyeni; Taufiq, Abdul Rahman; Numan, Muhammad; Faiz, Muhammad; Saputra, Edriagus; Masruri, Muhammad (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2023)
The objective of the study is to analyze the method of Badiuzzaman Sa’id Nursi to understand Hadiths in Kitab Rasail Al-Nur. The hadiths are mostly related to aqidah, charity motivation, and confusion (syubhat) between the materialist group and ahl kitab in understanding the hadith. The hermeneutic approach of the qualitative method is employed in this study in which both the objective aspect (hadiths in the kitab of Rasail Al Nur) and the subjective aspect (the thought background of Said Nursi) are analyzed. The data of the study is the hadiths in the Kitab Rasail Al-Nur of Chapter One al-Kalimat, chapter two al-Maktubat, chapter three al-Lama’at, and chapter four Al-Syuat. Then the data is thematically analyzed by using the NVivo 12 and it is revealed that there are twelve methods of Said Nursi to understand hadiths in the book of Rasail Al-Nur, namely: i) Al-Din al-Imtihan (Religion is an exam); ii) Thabaqah Masail al-Islamiyah (Various issues in Islam have different levels and positions); iii) Ma’lumat Ulama Ahl al-Kitab (Information for ahl kitab Christians and Jews); iv) Al-Idraj (Insertion or Merging); v) Al-Ilham (Inspiration); vi) Al-Amtsal (analogy); vii) Al-Tasybihat al-Balaghiyah (rhetorical parables); viii) Hikmah al-Ikhfa’ (wisdom of hiding); ix) Wijhah al-Masail al-Imaniyah (some perspectives on some faith issues); x) Balaghah al-Irsyad (rhetoric art of giving guidance); xi) Al-Mutasyabihat (the resemblance); xii) Ikhtilaf Zawiyah al-Nazhar (different perspectives). The finding could be initial data for further analysis to study different issues in similar contexts.